Analisis Kesetaraan Gender pada Kata Ganti Orang dalam Bahasa Arab dan Sunda - Akmaliyah Akmaliyah (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
Language is a product of community culture that affects society and is influenced by society. Language is related to the values of gender equality because the construction of society towards gender equality can be done through the socialization of language, one of which is arabic pronouns and Sundanese. Language can affect the value of gender equality can also affect language products. This paper analyzes descriptions and information and balancing values to explain those values.